Demographic and socio-demographic profile of people living with HIV/AIDS - Jainara Maria Vieira Galvão, Ana Carla Marques da Costa, Jaime Vieira Galvão (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v6i1.5533